Tissue alarmins and adaptive cytokine induce dynamic and distinct transcriptional responses in tissue-resident intraepithelial cytotoxic T lymphocytes. Issue 108 (March 2020) - Zorro, Maria Magdalena; Aguirre-Gamboa, Raul; Mayassi, Toufic; Ciszewski, Cezary; Barisani, Donatella; Hu, Shixian; Weersma, Rinse K; Withoff, Sebo; Li, Yang; Wijmenga, Cisca; Jabri, Bana; Jonkers, Iris H
Abstract: The respective effects of tissue alarmins interleukin (IL)-15 and interferon beta (IFNβ), and IL-21 produced by T cells on the reprogramming of cytotoxic T lymphocytes (CTLs) that cause tissue destruction in celiac disease is poorly understood. Transcriptomic and epigenetic profiling of primary intestinal CTLs showed massive and distinct temporal transcriptional changes in response to tissue alarmins, while the impact of IL-21 was limited. Only anti-viral pathways were induced in response to all the three stimuli, albeit with differences in dynamics and strength. Moreover, changes in gene expression were primarily independent of changes in H3K27ac, suggesting that other regulatory mechanisms drive the robust transcriptional response. Finally, we found that IL-15/IFNβ/IL-21 transcriptional signatures could be linked to transcriptional alterations in risk loci for complex immune diseases. Together these results provide new insights into molecular mechanisms that fuel the activation of CTLs under conditions that emulate the inflammatory environment in patients with autoimmune diseases. Highlights: We report the epigenetic and transcriptomic response of IE-CTLs to tissue-derived alarmins and adaptive cytokine. IL-15 and IFNβ induce massive and distinct transcriptional changes in IE-CTLs, while the impact of IL-21 was limited. Genes associated with immune-mediated intestinal diseases are enriched in genes responding to IL-15, IFNβ and IL-21 in IE-CTLs.